Lymphopenia in Esophageal Cancer: What Have We Learned? - Wang, Jia-Lin; Ma, Rong; Kong, Wei; Zhao, Ren; Wang, Yan-Yang (Frontiers in Oncology, 2021)
Lymphopenia caused by disease or treatment is frequent in patients with cancer, which seriously affects the prognosis of these patients. Immune checkpoint inhibitors (ICIs) have garnered attention as one of the most promising strategies for the treatment of esophageal cancer (EC). The status of the immune system, such as, the lymphocyte count, is now considered to be an important biomarker for ICI treatments. Recognition of the significant impact of the lymphocyte count on the survival of patients with EC in the era of immunotherapy has revived interest in understanding the causes of lymphopenia and in developing strategies to predict, prevent and eliminate the adverse effect of lymphopenia. Here, we review what we have learned about lymphopenia in EC, including the prognostic and predictive value of lymphopenia in patients with EC, the predictors of lymphopenia, and the strategies to ameliorate the effect of lymphopenia in patients with EC.